Feasibility of the recent recommendations for the establishment of corporate voluntary arrangement ('CVA') by corporate law reform committee (CLRC) in solving insolvency issues: A case study of abandoned housing projects in Malaysia - Md Dahlan, Nuarrual Hilal (2012)
The Malaysian Corporate Law Reform Committee (CLRC)consists of 25 persons from various backgrounds such as advocate & solicitors, representatives from the Companies Commission of Malaysia (CCM), Securities Commission (SC),Bursa Malaysia Securities Berhad, Prime Minister's Department, Attorney General Office, Insolvency Department, company secretaries, chartered accountants and academics. CLRC is also supported by several working groups' members and a secretariat.CLRC has conducted a research into the current provisions under the Companies Act 1965 since December 2003 which took about four years to complete. The result is the Final Report of the CLRC.Under this report, the CLRC has recommended the establishment of Corporate Voluntary Arrangement ('CVA') to take over the affairs of the insolvent companies and rescue them. The CVA is armed with a moratorium power against any action taken which may be commenced by the creditors and others to enable him to effectively carry out his duty in order to prepare a restructuring plan acceptable by the creditors.The plan also must be approved by the Court.This paper is a result of a pure qualitative legal research that relates to the abandoned housing projects in Malaysia.The authors also analyzed the CVA's provisions as recommended by the CLRC for the establishment of CVA vis-a-vis the rehabilitation of abandoned housing projects.The objective of this paper is to study the feasibility of the establishment and powers of the CVA in dealing with the rehabilitation of abandoned housing projects and in protecting the rights of the purchasers.Through this writing, the authors are of the view that, the recommendation of the CLRC for the appointment of CVA is commendable.Nonetheless, it is submitted that, in the case of abandoned housing projects, despite having statutory and legal powers as recommended by the CLRC, the proposed CVA still cannot fully provide comprehensive solution in the rehabilitation of abandoned housing projects. Let alone to protect the purchasers' interests.This paper suggests certain legal approaches to improve the rehabilitation mechanism of abandoned housing projects purportedly to be carried out by the CVA and for protecting the rights and interests of the stakeholders.